Psychotropic drug use rate among detention house residents and association with the category of the crimes in Japan - Nishio, Akihiro (Neuropsychopharmacology reports, 2021)
Aim The White Paper on Crime 2019 from the Japanese Ministry of Justice reported that the percentage of crimes committed by people with mental disabilities was only 1.0%. In contrast, the findings of a statistical survey of correctional facilities reported that 15.1% of the prisoners were diagnosed with a mental illness. This study aimed at clarifying the relationship between mental illness and crime among suspects in a detention house and explaining this large gap. Methods Criminal suspects who were newly admitted in the Gifu detention house in Japan were eligible for the study. The status of psychotropic drug use was investigated, and its relationship with age, sex, offense history, and type of crime was analyzed. Newly prescribed medications in detention houses or police stations were excluded. Results In total, 26.5% of the residents in a detention house used psychotropic drugs. The psychotropic drug use rate was 16.7% (excluding the sleeping pill use rate). The use rates of sleeping pills, anxiolytics, antidepressants, and antipsychotics were 22.6%, 11.1%, 3.0%, and 9.6%, respectively. Psychotropic drug use was high in illicit drug users and low in suspects for immigration violence. Psychotropic drug use was higher among female suspects, suspects in their 40s and 50s, and suspects with a multiple crime history. Anxiolytic (17.0%) and antipsychotic (11.9%) use rates were high among suspects for violence. Conclusion In total, 26.5% of the subjects used psychotropic drugs. Psychotropic drug use was high in illicit drug users and low in suspects for immigration violence. In total, 26.5% of the residents in a detention house used psychotropic drugs. The psychotropic drug use rate was 16.7% (excluding the sleeping pill use rate). The use rates of sleeping pills, anxiolytics, antidepressants, and antipsychotics were 22.6%, 11.1%, 3.0%, and 9.6%, respectively.